Indonesian International Students’ Identity Post Mobility: How Mobility Affects International Students Beyond Education - Yosephine Carolina Nugraha (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2022)
As part of the skilled labor group, international students have quite a high potential to decide their country’s future direction. This means there is a need for deeper understanding regarding the views and identity of international students, which are affected by their study tenure abroad. As such, this paper aims to shed new light on how mobility as a form of migration affected the identity of Indonesian international students as a group of migrants. To achieve this purpose, five international students from Indonesia, both current and former, were interviewed in-depth to understand these post-mobility changes in their identity. From these interviews, it was revealed that their experience abroad, not exactly the mobility act itself, is the one with more impact on their identity. Most expressed that their time abroad has changed their perspective and general world-view, such as they feel more like are global citizens or more concerned about environmental and humanity issues. In turn, even though their Indonesian root is still visible, sometimes they are also seen as akin to a stranger in their own home.